Finns det en relation mellan arbetsklimat och en individs självförmåga och självmedkänsla? - Topgaard,Thea; Savelind,Annika (2025)
The purpose of this study was to investigate whether there was a relationship between the work climate and employees’ self-efficacy and self-compassion. Also, possible differences between the level of these variables, based on how long the respondents had been at their workplace, were investigated. The study was conducted through a survey where 130 participants (68 women, 62 men) were asked to self-assess their work climate, self-efficacy and self-compassion. The survey was directed at individuals who have been at their current workplace for at least three months and with a service rate of at least 50% of the normally expected service rate. The result showed a significant relationship between the work climate and the employees’ self-compassion, while there was no relationship between the work climate and the employees’ self-efficacy. This indicates a possible impact of the work climate on an employee's self-compassion. The results also showed that those who had been at a workplace for a longer period of time had higher self-compassion than those who had not been there as long. This result was not found concerning self-efficacy. Further research is recommended to leave out influences from other factors.
Keywords: arbetsklimat; självförmåga; självmedkänsla; välmående workplace climate; organizational climate; self-efficacy; self-compassion; well-being